A layered electrospun and woven surgical scaffold to enhance endogenous tendon repair. (15th October 2015) - Hakimi, O.; Mouthuy, P.A.; Zargar, N.; Lostis, E.; Morrey, M.; Carr, A.
Graphical abstract: Abstract: Surgical reattachments of tendon to bone in the rotator cuff are reported to fail in around 40% of cases. There are no adequate solutions to improve tendon healing currently available. Electrospun, sub-micron materials, have been extensively studied as scaffolds for tendon repair with promising results, but are too weak to be surgically implanted or to mechanically support the healing tendon. To address this, we developed a bonding technique that enables the processing of electrospun sheets into multi-layered, robust, implantable fabrics. Here, we show a first prototype scaffold created with this method, where an electrospun sheet was reinforced with a woven layer. The resulting scaffold presents a maximum suture pull out strength of 167 N, closely matched with human rotator cuff tendons, and the desired nanofibre-mediated bioactivity in vitro and in vivo . This type of scaffold has potential for broader application for augmenting other soft tissues.